SYNTHESIS, CHARACTERIZATION AND STRUCTURAL STUDIES OF NEW N2S2 SCHIFF BASELIGAND AND ITS COORDINATION COMPLEXES WITH SOME TRANSITION METAL IONS. - Al-Karawi, Ahmed (Iraqi Journal of Science, 2024)
New Schiff base tetradentate ligand with type (N2S2): 1,3-isophthaldehyde bis(4–methyl 3-thiosemicarbazone)(ISMTSC) has been prepared. Synthesis was carried out by the condensation of 1,3-isophthaldehyde and 4-methyl 3-thiosemicarbazide in mole ratios of (1:2) respectively and under nitrogen atmosphere. The ligand has been characterized and its structure was elucidated depending upon microelemental analysis (CHN), spectral data (I.R, U.V–Vis, 1H, 13CNMR and mass spectrum). Series of metal complexes of the ligand with metal ions such as CoII, NiII, CuII, CdII and HgII have been synthesized by adding (1 mm mole) of (ISMTSC) to the methanolic solution (1 mm mole) of metal salts. The complexes were characterised and their stereochemical structures and geometries were suggested depending upon data of microelemental analysis (CHN), spectral studies (I.R, UV–Vis) , 1H and 13C NMR for [CdII(ISMTSC) (H2O)2] mass spectrum for [CuII(ISMTSC)(H2O)2] as well as magnetic moments and conductivity measurements. The following general formula were achieved: [M(ISMTSC)(H2O)2] where M = Co(II) ,Cu(II) and Cd(II), and [M(ISMTSC)] where M = Ni(II) and Hg(II) ions. The electronic spectra in DMF (10–3 M) supported by magnetic moments in solid state revealed octahedral geometries for the Co(II),Cu(II) and Cd(II) complexes, square planer geometry for Ni(II) complegeometry for the Hg(II) complex. Conductivity measurements of the new synthesized